2011
DOI: 10.12968/bjom.2011.19.2.116
|View full text |Cite
|
Sign up to set email alerts
|

A bereavement and communication study day for midwives

Abstract: Following the loss of a baby, women and their families have particular needs. As midwives are the main professional group present at this time, they need to support women through the process. However, it may be relatively rare for midwives to encounter bereavement, and so it is important to ensure that competency is maintained in this area. This has been demonstrated by an increasing demand for additional training from midwives, which led to a bereavement and communication study day within the University Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The findings from the survey in phase one (section 4.2.1) also support the literature where it is noted that provision of perinatal bereavement training and then bereavement care is not consistent (Siassakos, Jackson, Gleeson et al, 2017;Hollins Martin, Forrest, Wylie et al, 2013;Baxter and Baron, 2011). The findings from phase one serve to confirm these findings and further support the need for change to address this.…”
Section: Existing Education Provision and Gapssupporting
confidence: 63%
See 3 more Smart Citations
“…The findings from the survey in phase one (section 4.2.1) also support the literature where it is noted that provision of perinatal bereavement training and then bereavement care is not consistent (Siassakos, Jackson, Gleeson et al, 2017;Hollins Martin, Forrest, Wylie et al, 2013;Baxter and Baron, 2011). The findings from phase one serve to confirm these findings and further support the need for change to address this.…”
Section: Existing Education Provision and Gapssupporting
confidence: 63%
“…Bereavement care training was not something that was given priority in clinical practice as the demands of updating annually on mandatory training had to take priority (Baxter and Baron, 2011). The SANDS audit (2016) found that only 46% of Trusts had this as part of their mandatory training.…”
Section: Bereavement Care Trainingmentioning
confidence: 99%
See 2 more Smart Citations